Phenotypes of Pinus sylvestris are more coordinated under local harsher conditions across Europe. (10th May 2021) - Benavides, Raquel; Carvalho, Bárbara; Matesanz, Silvia; Bastias, Cristina C.; Cavers, Stephen; Escudero, Adrián; Fonti, Patrick; Martínez‐Sancho, Elisabet; Valladares, Fernando
Abstract: Plant species that grow across environmental gradients show a range of trait expression, but traits do not vary independently. In fact, phenotypes are integrated expressions of multiple traits that covary due to trade‐offs among functions and processes. Understanding trait covariation structures will ultimately help with predicting species' responses to change and developing management actions. We measured variation and covariation (a proxy of phenotypic integration) among functional traits of Pinus sylvestris from paired populations across its European distribution. Populations within a pair were close enough to be in gene flow contact but located in contrasting environmental conditions across a local gradient. Measured traits represented three axes of variation (groups of traits) related to a tree's competitive ability and the trade‐off between resource acquisition and conservation, namely plant size measures and stem and foliar traits. Results revealed important intra‐ and inter‐population trait variability. In particular, at the population level, trait means shifted across the climatic gradient mainly described by mean annual temperature. Moreover, we found a higher degree of trait covariation in populations under harsher environments (i.e. lower environmental suitability for the species). This pattern was consistent within population pairs, suggesting that higher trait covariation may be adaptive, being more coordinated in sites with harsher conditions. At larger spatial scales, we found a less conclusive pattern with a trend of increasing covariation at the northern edge of the species distribution. This result suggests that at larger scales different processes may be involved in the trade‐off between the adaptive value of phenotypic covariation versus its constraints on trait combinations that may limit plant's response capability. Synthesis . Trait covariation varies at different spatial scales, increasing under harsher conditions, and the robustness and repeatability of this pattern suggests its adaptive role for the species' responses to different environments. Abstract : Trait covariation varies at different spatial scales, increasing under harsher conditions, and the robustness and repeatability of this pattern suggests its adaptive role for the species' responses to different environments. Resumen: Las especies vegetales muestran diferencias en la expresión de sus rasgos a lo largo de gradientes ambientales; sin embargo, éstos no varían de manera independiente. El fenotipo es la expresión integrada de rasgos que covarían debido a los distintos procesos bajo las condiciones a los que están sometidos. Comprender la estructura de covariación entre rasgos puede ayudar a predecir la respuesta de las especies frente a los cambios y a anticipar medidas de gestión frente a los mismos. En este trabajo, hemos medido la variación y covariación (aproximación a la integración fenotípica) entre rasgos funcionales en individuos de Pinus sylvestris procedentes de pares de poblaciones a lo largo de su área de distribución europea. Las poblaciones dentro de una pareja estaban lo suficientemente cerca para asumir flujo genético entre ellas, pero localizadas en condiciones contrastadas en un gradiente local. En cada población medimos rasgos funcionales pertenecientes a tres ejes de variación relacionados con la capacidad competitiva del individuo y de la economía de los recursos (el equilibrio entre la adquisición y conservación de recursos), en concreto medidas de tamaño de la planta y rasgos medidos en tronco y hojas. Los resultados revelaron una importante variabilidad de rasgos a nivel intra‐ e inter‐poblacional. En concreto, la media poblacional de la mayoría de los rasgos varió a lo largo del gradiente climático definido principalmente por la temperatura media anual. Además, encontramos un grado de covariación de rasgos mayor en poblaciones bajo condiciones ambientales más duras (i.e. con menor idoneidad ambiental para la especie). Este patrón fue consistente entre parejas de poblaciones, sugiriendo que la covariación de rasgos puede ser adaptativa apareciendo fenotipos más coordinados en ambientes menos favorables. A escala espacial mayor, encontramos una tendencia con mayor covariación en el extremo norte del área de distribución. Este resultado asimétrico entre los extremos de la distribución, aunque no concluyente, indica que a grandes escalas otros procesos pueden intervenir en el balance entre el valor adaptativo de la covariación y la limitación que impone en la combinación de rasgos que pueden mermar la capacidad de respuesta frente a cambios. Síntesis . la covariación de rasgos varía a diferentes escalas espaciales, incrementándose en condiciones estresantes. La robustez de dicho patrón sugiere su papel adaptativo en la respuesta de las especies frente a diferentes ambientes.